MOS principles - revisited - Ismail, Izzati Nabilah Ismail (2018)
This lecture is directed to young oral surgeons and dental officers in which it gives an overview of the prevalence & the public health aspects of minor oral surgery in Malaysia. It then revisits and discuss the principles in minor oral surgery including the indications and decision making, surgical principles, presurgical assessment, the clinical and radiological assessment, the risk assessment, grading the difficulty index of the surgery, the medications used, alternative procedures available as well as the complications. At the end of the lecture, participants are expected to grab the basic principles in doing minor oral surgery.